IMPLEMENTASI KURIKULULUM MERDEKA DI SEKOLAH DASAR AJARAN 2022/2023 - Goni, Agnes; Paila, Sefanya Orysha (DIKSAR : Jurnal Pendidikan Dasar, 2023)
The purpose of this research is to understand the planning, implementation, and assessment of the Merdeka Curriculum learning at SD Advent Remboken. This research was conducted at SD Advent Remboken using a descriptive qualitative research approach. The results of the research are as follows: in lesson planning, teachers use teaching materials that are appropriate and refer to the teaching materials provided by the Ministry of Education and Culture, with the option to modify them independently. The learning implemented by teachers follows the principles of learning in the Merdeka Curriculum and is in the developing stage, considering that the implemented learning is student-centered and the appropriateness of the learning methods used. Assessment is conducted based on the principles launched by the Ministry of Education and Culture